2016
DOI: 10.1264/jsme2.me16066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated CO<sub>2</sub> Concentration, Elevated Temperature and No Nitrogen Fertilization on Methanogenic Archaeal and Methane-Oxidizing Bacterial Community Structures in Paddy Soil

Abstract: Elevated concentrations of atmospheric CO2 ([CO2]) enhance the production and emission of methane in paddy fields. In the present study, the effects of elevated [CO2], elevated temperature (ET), and no nitrogen fertilization (LN) on methanogenic archaeal and methane-oxidizing bacterial community structures in a free-air CO2 enrichment (FACE) experimental paddy field were investigated by PCR-DGGE and real-time quantitative PCR. Soil samples were collected from the upper and lower soil layers at the rice panicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In this study, the difference in the mcr A gene abundance in the three compartments of both marshes was statistically not significant under elevated CO 2 when compared to ambient CO 2 . In a previous paddy soil study, Liu et al (2016) similarly did not observe an effect of elevated CO 2 on the abundance of the methanogenic archaeal community in the bulk soil. In contrast, some studies have reported that elevated CO 2 significantly increased the abundance of methanogenic archaea in rice cultivated soil ( Inubushi et al, 2003 ; Okubo et al, 2015 ) because of the increase in the carbon supply as root exudates with elevated CO 2 ( Bhattacharyya et al, 2013 ).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In this study, the difference in the mcr A gene abundance in the three compartments of both marshes was statistically not significant under elevated CO 2 when compared to ambient CO 2 . In a previous paddy soil study, Liu et al (2016) similarly did not observe an effect of elevated CO 2 on the abundance of the methanogenic archaeal community in the bulk soil. In contrast, some studies have reported that elevated CO 2 significantly increased the abundance of methanogenic archaea in rice cultivated soil ( Inubushi et al, 2003 ; Okubo et al, 2015 ) because of the increase in the carbon supply as root exudates with elevated CO 2 ( Bhattacharyya et al, 2013 ).…”
Section: Discussionmentioning
confidence: 56%
“…Studying a temperate marsh microcosm, Lee et al (2012) found that elevated CO 2 concentrations increased the relative abundance of hydrogenotrophic methanogens. In contrast, other studies did not identify any apparent effect on the methanogen community ( Angel et al, 2012 ; Liu et al, 2016 ). Drigo et al (2008) found that elevated atmospheric CO 2 did not affect the microbial community in the bulk soil, but did near the roots.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Liu et al [63] also observed that the abundance of methane-oxidizing bacteria significantly decreased under higher temperature. The decrease observed in the abundance of methane-oxidizing bacteria may be related to increased methane emission under climate warming [74].…”
Section: Response Of Soil Carbon and Nitrogen Cycling Genes Abundancementioning
confidence: 97%
“…The amount of methane released into the atmosphere is tightly controlled by the balance between microbial methane production and oxidation by methane-producing archaea and methane-oxidizing bacteria, respectively. Based on the observation that increased CO 2 levels in the atmosphere promote the production and emission of methane from rice paddies, Liu and colleagues investigated the effects of increased CO 2 levels, elevated soil temperatures, and the absence of nitrogen fertilization on methane-producing and -oxidizing microbial populations in a free-air CO 2 enrichment (FACE) experimental paddy field ( 20 ). Using PCR with denaturing gradient gel electrophoresis (DDGE) and quantitative PCR techniques targeting the genes mcrA and pmoA , which encode key enzymes for methane production and oxidization, they showed that the abundance of methane-producing archaea, detected as mcrA gene abundance, was not affected by increased CO 2 levels and elevated soil temperatures, but by the absence of nitrogen fertilizer, leading to low abundance.…”
mentioning
confidence: 99%